Analysis of the Impact Renaissance Dam Construction Toward Stability Nile River in Egypt - Muhammad Ali Ashhabul Kahfi; Mohammad Izdiyan Muttaqin (Universitas Muhammadiyah Gorontalo, 2022)
The Nile River is a vital lifeline for countries in East and North Africa, particularly Egypt, Sudan, and Ethiopia. Ethiopia's construction of the Great Renaissance Dam (GERD) since 2011 has raised serious concerns, particularly in Egypt, over concerns it will reduce the flow of water vital to the country's livelihoods and economic stability. This article aims to analyze the geopolitical impact of water on the construction of the Great Renaissance Dam in Ethiopia and its relation to the stability of the Nile in Egypt. The geopolitical impact of water is related to the potential reduction of Nile water flow, which can affect the availability of water for agriculture and water consumption downstream. The method used is qualitative descriptive analysis by collecting data from primary and secondary sources. The results of the analysis show that the geopolitical impact of water can affect regional stability in the Middle East and North Africa region, as well as impact the availability of water downstream and the stability of the Nile River in Egypt. A diplomatic solution is needed to overcome differences of views and reach an agreement that can meet the water needs of the affected region.